Drilling engineering problems and solutions a field guide for engineers and students - Hossain, M. Enamul; Islam, Rafiqul 1959- (Wiley-Scrivener, 2018)
"Petroleum and natural gas still remain the single biggest resource for energy on earth; Even as alternative and renewable sources are developed, petroleum and natural gas continue to be, by far, the most used and, if engineered properly, the most cost-effective and efficient, source of energy on the planet; Drilling engineering is one of the most important links in the energy chain, being, after all, the science of getting the resources out of the ground for processing; Without drilling engineering, there would be no gasoline, jet fuel, and the myriad of other have to have products that people use all over the world every day; Following up on their previous books, also available from Wiley-Scrivener, the authors, two of the most well-respected, prolific, and progressive drilling engineers in the industry, offer this groundbreaking volume; They cover the basics tenets of drilling engineering, the most common problems that the drilling engineer faces day to day, and cutting-edge new technology and processes through their unique lens; Written to reflect the new, changing world that we live in, this fascinating new volume offers a treasure of knowledge for the veteran engineer, new hire, or student; This book is an excellent resource for petroleum engineering students, reservoir engineers, supervisors & managers, researchers and environmental engineers for planning every aspect of rig operations in the most sustainable, environmentally responsible manner, using the most up-to-date technological advancements in equipment and processes"--
Includes bibliographical references and index
Keywords: Oil well drilling / Handbooks, manuals, etc; Oil well drilling; Handbooks and manuals; SCIENCE; Energy